Reduction of methotrexate and glucocorticoids use after the introduction of biological disease-modifying anti-rheumatic drugs in patients with rheumatoid arthritis in daily practice based on the IORRA cohort. Issue 3 (4th May 2018) - Shimizu, Yoko; Tanaka, Eiichi; Inoue, Eisuke; Shidara, Kumi; Sugimoto, Naoki; Seto, Yohei; Nakajima, Ayako; Momohara, Shigeki; Taniguchi, Atsuo; Yamanaka, Hisashi
Abstract: Objectives: To evaluate usage patterns for methotrexate (MTX) and/or glucocorticoids in rheumatoid arthritis (RA) patients receiving biological disease-modifying antirheumatic drugs (bDMARDs) in daily practice. Methods: Data from RA patients who commenced treatment with bDMARDs (infliximab [IFX], etanercept [ETN], tocilizumab [TCZ], or adalimumab [ADA]) from 2008 to 2010 were extracted from the Institute of Rheumatology, Rheumatoid Arthritis (IORRA) database. The proportions of patients taking concomitant MTX and glucocorticoids and doses of these medications were evaluated before and 2 years after initiation of each bDMARD. Results: A total of 470 RA patients who had initiated a bDMARD (IFX: n = 98, ETN: n = 181, TCZ: n = 90, and ADA: n = 101) were evaluated. The proportion of patients taking MTX decreased over time among ETN and TCZ users, while it increased among ADA users. The MTX dose decreased over time among IFX, ETN, and TCZ users, but not among ADA users. Although the rate of glucocorticoid use and dose decreased after bDMARD initiation in all four bDMARD groups, approximately 50% of patients continued to receive glucocorticoids 2 years after bDMARD initiation. Conclusion: MTX and glucocorticoid use and doses in daily practice were commonly reduced after the initiation of bDMARDs, with the dose adjustment varied depending on the bDMARD.